Web-Based Vocational High School Financial Administration Information System Using Laravel Framework - Riskianus Japa Loka; Adelbertus Umbu Jangais; Karolus Wulla Rato (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The use of Information and Communication Technology (ICT) can be applied to various aspects to facilitate human work which was originally done manually to become a computerized system. One example is in the field of administrative services in various agencies, schools are one example of agencies that still use manual administration systems. Currently schools record and manage. Payment and expenditure data are processed through computers, however basic data management tools like Microsoft Office Excel are still used and not fully integrated. problems are frequently faced, such as data inaccuracies, errors in capturing data, challenges in finding data owing to time constraints, and loss or damage to data resulting from storage, so making the process less effective and efficient.The software used to build this system is a MySQL database, PHP programming language, HTTP Server namely AppServ Version 2.5.5, Web Browser namely Internet Explorer and Macromedia Dreamweawer editor. This system will produce information in the form of Web-Based Vocational High School Financial Administration Using the Laravel Framework